Tunneling nanotubes and mesenchymal stem cells: New insights into the role of melatonin in neuronal recovery. Issue 1 (22nd April 2022) - Luchetti, Francesca; Carloni, Silvia; Nasoni, Maria G.; Reiter, Russel J.; Balduini, Walter
Abstract: Efficient cell‐to‐cell communication is essential for tissue development, homeostasis, and the maintenance of cellular functions after injury. Tunneling nanotubes (TNTs) have emerged as a new important method of cell‐to‐cell communication. TNTs are primarily established between stressed and unstressed cells and can transport a variety of cellular components. Mitochondria are important trafficked entities through TNTs. Transcellular mitochondria transfer permits the incorporation of healthy mitochondria into the endogenous network of recipient cells, changing the bioenergetic profile and other functional properties of the recipient and may allow the recipient cells to recuperate from apoptotic processes and return to a normal operating state. Mesenchymal cells (MSCs) can form TNTs and transfer mitochondria and other constituents to target cells. This occurs under both physiological and pathological conditions, leading to changes in cellular energy metabolism and functions. This review summarizes the newly described capacity of melatonin to improve mitochondrial fusion/fission dynamics and promote TNT formation. This new evidence suggests that melatonin's protective effects could be attributed to its ability to prevent mitochondrial damage in injured cells, reduce senescence, and promote anastasis, a natural cell recovery phenomenon that rescues cells from the brink of death. The modulation of these new routes of intercellular communication by melatonin could play a key role in increasing the therapeutic potential of MSCs.